Book Reviews (The ecumenical review, 1972)
Book reviewed in this article: CONCILIARITY PAST AND PRESENT: Councils and Assemblies, ed. G. J. Cuming and Derek Baker CONCILIARITY PAST AND PRESENT: “La Structure Synodale de l'Eglise dans la Théologie orientale”, by Pierre Duprey CCIA RETROSPECT: The Churches and the Nations, by Dr. O. Frederick Nolde, with foreword by Dr. W. A. Visser 't Hooft AN ECUMENICAL PIONEER: Alphonse Koechlin, pasteur et chef d'Eglise. Préface de W. A. Visser 't Hooft, by Henri d'Espine THE INFALLIBILITY DEBATE CHURCH AND SOCIETY THE DEBATE CONTINUES: Technology and Social Justice, by Ronald H. Preston (ed.)